Evaluation of Grapevine Production in the World and in the Czech Republic, An Issue of Global Wine-Making Power - Kamila Veselá; Lucie Severová (Communications of International Proceedings, 2020)
In vino veritas – “in wine lies the truth” - and it is also true that for centuries wine has belonged among the most popular consumer commodities all over the world, a state of affairs which will probably not change much in the future. Wine production represents an important item in the gross domestic product (GDP) of many economies. In the long term, Italy, Spain and France are undoubtedly among the most significant wine producers, as well as the largest exporters of this commodity. Many studies have been carried out regarding the impact of wine consumption on human health, and several positive influences have been established. This fact probably plays its role in wine consumption. The aim of this text is to evaluate world grape production and wine consumption and to characterize the changing positions of the largest producers and exporters. The article uses time series analysis on the development of grape production, the export and import of grapes, and subsequently wine consumption, in order to analyse and evaluate the role of different countries and their positions on the grape market. Both absolute and relative indicators, as well as the trends of these indicators, are evaluated in the time series analysis. The United States of America, France and Germany can be counted among the countries with the highest wine consumption. They have strong leading positions on the global wine market and therefore they significantly influence its pricing policy.
Keywords: Czech Republic; GDP; wine; vine; harvest; production.